2011
DOI: 10.1002/pc.21227
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial micromechanics and effect of moisture on fluorinated epoxy carbon fiber composites

Abstract: Carbon fiber composites have witnessed an increased application in aerospace and other civil structures due to their excellent structural properties such as specific strength and stiffness. However, unlike other structural materials, carbon fiber composites have not been as widely studied. Hence, their increased application is also accompanied with a serious concern about their long‐term durability. Many of these applications are exposed to multiple environments such as moisture, temperature, and UV radiation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…These results differ from those of Pandey et al [12] and Biro et al [30] on carbon/epoxy systems respectively immersed in boiling water and water at 80°C. Biro et al [30] found an increase in friction strength (by more than 200%) and in the friction contribution to τ app after immersion.…”
Section: Evolution Of the Friction Strengthcontrasting
confidence: 95%
See 1 more Smart Citation
“…These results differ from those of Pandey et al [12] and Biro et al [30] on carbon/epoxy systems respectively immersed in boiling water and water at 80°C. Biro et al [30] found an increase in friction strength (by more than 200%) and in the friction contribution to τ app after immersion.…”
Section: Evolution Of the Friction Strengthcontrasting
confidence: 95%
“…For example, debonding of micro-droplets was used by Zinck et al [11] who showed a decrease in critical strain energy release rate during the first 50 hours of aging (60°C and 98% RH) of glass/epoxy systems . Pandey et al [12] showed a drop in apparent shear strength on carbon/epoxy composites, from 88 to 80 MPa after immersion in boiling water for 48h. They explained this by radial stresses relaxation during immersion.…”
Section: Introductionmentioning
confidence: 99%
“…One important group of polymeric composites is based on carbon fiber reinforcing systems which is often used in weight reduction and high specific strength requirement, i.e., aerospace, automotive, ballistic armor, or extreme sport applications. In addition, an improvement of polymeric material properties particularly by modification of the existing polymers to achieve high thermal properties, i.e., high char yield, and high glass transition temperature ( T g ) becomes increasingly important for an fiber‐reinforced polymer composites . Recently, the developed polybenzoxazine are a novel class of thermosetting polymers that combined the thermal properties and flame retardance of phenolic resin with mechanical performance and molecular design flexibility of epoxy resin.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a few microscopic mechanical testing methods have been developed to investigate the fundamental mechanical properties of interphase between fiber and matrix, including single fiber push-out test [21][22][23], fiber fragmentation test [24,25], and single fiber microbond test [26][27][28], among which it is found that the specimens for the microbond test are more efficient to achieve a good soaking of polymer matrix and fiber/matrix interface due to the small volume of resin droplet size [19,29].…”
Section: Introductionmentioning
confidence: 99%
“…However, these macro-level characterizations are influenced to a large extent by the moisture resistance of matrix materials and the geometrical feature of composites, which may disturb the study on the properties of fiber/matrix interface [19,20].…”
Section: Introductionmentioning
confidence: 99%